The Modernity of Naga Village Community: Social Change Study through Visual Media Analysis - Agus Setiawan (Universitas Pasundan, 2022)
Looking at the cultural area landscape, Tatar Sunda certainly inherited different rich culture then other regions. Not only inherited tangible cultural wealth but also intangible cultural wealth. However, in the midst of an increasingly advanced civilization, now the Sundanese cultural heritage has changed its existence. Functionally many spiritual traditional cultural products have been replaced by commercial modern cultural products. This fenomenon can be studied from the social changes that occured in Kampung Naga in Tasikmalaya regencies, although in the one hand still maintains its traditional values, on the other hand this traditional village has undergone in many changes. The study intends to determine the existence of Sundanese cultural products, as well as products of national culture in general from the influence of the development of modernism. In addition, by examining the phenomenon of community life in the traditional village of Kampung Naga, it is hoped that the indicators that cause these changes will be known. All objects of this study will be investigated using the qualitative-interpretive methods. This study uses cultural theory, Social Change theory, and semiotic theory as the main reference literature. The data sources used are main (primary) data and secondary data. The main data was obtained directly through interviews with the people of Kampung Naga. Meanwhile, secondary data was obtained from written sources such as: books from previous research, scientific journals, personal documents, photos, statistics, audio and video recordings. Therefore, starting from these initial observations, at least the root cause of social change in Kampung Naga can be described, and its cannot be separated from both internal and external factors behind it, for example: 1) The influence of global modernization, 2) The influence of modernization brought by the people of Kampung Naga who live outside the Traditional Village, 3) The adaptive attitude of the Kampung Naga people living in the Traditional Village. 4) Economic demands and community welfare. These factors are the main source of modernism in Kampung Naga.